How to Care for Adolescent Patients With Orthostatic Intolerance in the Primary Care Office - Camden Hebson; Kelly Muterspaw; Alexander Kuo; Polly Borasino; Khalisa Syeda; Toren Anderson (Journal of Primary Care & Community Health, 2024)
Orthostatic intolerance (and its subtype postural orthostatic tachycardia syndrome [POTS]) is an increasingly common complaint among adolescents associated with significant decrease in quality of life and frequent visits to primary care offices. As orthostatic intolerance becomes increasingly discussed online and through social media, we have observed that family angst and anxiety only heighten, often leading to requests for specialist referral to manage the symptoms. This often leads to delay in diagnosis, which further exacerbates the situation. In truth, however, a pragmatic approach applied by the primary care provider, including a ready explanation for the experienced symptoms, not only provides the bedrock for patient improvement, but also eases the anxiety of having a seemingly nebulous diagnosis. As physicians caring for these patients, we have seen success with treatment and seek to share this blueprint. Key points that will be covered include how to make an accurate diagnosis (using the “dizziness rule”), how to counsel about treatment, and clinic pitfalls to avoid. The description of care that follows is not based on systematic review and instead is exactly what is used in our office and what we hope will be successful in yours as well.